82.9k views
4 votes
I need help with q 6​

I need help with q 6​-example-1

1 Answer

4 votes

9514 1404 393

Answer:

(A, B, C) = (-1, 2, 2)

Explanation:

Simplify the right side and equate coefficients of the x-terms.

x² -3 = A(x² +1) +(Bx +C)(x -1)

x² -3 = Ax² +A +Bx² -Bx +Cx -C

x² -3 = (A+B)x² +(C-B)x +(A-C) . . . . identify coefficients of each x-term

Matching coefficients on the left and right gives rise to three equations in the three unknowns:

A +B = 1

C -B = 0

A -C = -3

Adding all three equations, we get ...

(A +B) +(C -B) +(A -C) = (1) +(0) +(-3)

2A = -2

A = -1 . . . . . . divide by 2

B = 1 -A = 2

C = B = 2

The coefficients are ...

(A, B, C) = (-1, 2, 2)

User LexJacobs
by
5.6k points